2021
DOI: 10.3390/gels7040167
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and In-Vitro Characterization of pH-Responsive Semi-Interpenetrating Polymer Network Hydrogels for Controlled Release of Ketorolac Tromethamine

Abstract: Ketorolac tromethamine is a non-steroidal anti-inflammatory drug used in the management of severe pain. The half-life of Ketorolac tromethamine is within the range of 2.5–4 h. Hence, repeated doses of Ketorolac tromethamine are needed in a day to maintain the therapeutic level. However, taking several doses of Ketorolac tromethamine in a day generates certain complications, such as acute renal failure and gastrointestinal ulceration. Therefore, a polymeric-controlled drug delivery system is needed that could p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Disc thickness and diameter were also measured. Porosity was calculated using the following equation [ 51 ]: where ρ is the density of absolute ethanol, A1 is the dry hydrogel weight, A2 is the weight of the disc after removal from ethanol, and V represents the volume of the hydrogel following swelling.…”
Section: Methodsmentioning
confidence: 99%
“…Disc thickness and diameter were also measured. Porosity was calculated using the following equation [ 51 ]: where ρ is the density of absolute ethanol, A1 is the dry hydrogel weight, A2 is the weight of the disc after removal from ethanol, and V represents the volume of the hydrogel following swelling.…”
Section: Methodsmentioning
confidence: 99%
“…Ahmed A H Abdellatif et al., formulated cyclodextrin/adamantane-grafted polyethylene glycol-based self-assembling constructs for topical delivery of ketorolac tromethamine (Abdellatif et al., 2022 ). Yet another sustained and controlled systems of KT have been formulated into nanofibrils graft and polymer network hydrogels (Orasugh et al., 2019 ; Suhail et al., 2021 ). Priya Shahi et al., attempted to release KT chrono therapeutically by formulating microspheres and tablet in capsule system (Shahi et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Suhail et al 13 observed similar results for ketorolac release from carbopol 934/sodium poly(styrene sulfonateco-AAc) hydrogel. They explained that faster ketorolac release at neutral and alkaline pH is due to the deprotonation of the functional groups of hydrogel components.…”
Section: Resultsmentioning
confidence: 63%
“…In the special case of ketorolac, different polymeric matrixes have been used for absorption/release studies. [10][11][12] Suhail et al 13 synthesized composite hydrogels based on carbopol 934/sodium poly(styrene sulfonate-co-AAc), which was used for ketorolac absorption/release studies. They demonstrated that composite was pH sensitive by dynamic swelling and in vitro release studies at acidic and neutral pH (1.2 and 7.4, respectively), and that maximum swelling and higher ketorolac release was observed at pH 7.4.…”
Section: Introductionmentioning
confidence: 99%